Diagnosis of human fascioliasis by stool and blood techniques: update for the present global scenario. Issue 14 (31st July 2014) - MAS-COMA, S.; BARGUES, M. D.; VALERO, M. A.
SUMMARY: Before the 1990s, human fascioliasis diagnosis focused on individual patients in hospitals or health centres. Case reports were mainly from developed countries and usually concerned isolated human infection in animal endemic areas. From the mid-1990s onwards, due to the progressive description of human endemic areas and human infection reports in developing countries, but also new knowledge on clinical manifestations and pathology, new situations, hitherto neglected, entered in the global scenario. Human fascioliasis has proved to be pronouncedly more heterogeneous than previously thought, including different transmission patterns and epidemiological situations. Stool and blood techniques, the main tools for diagnosis in humans, have been improved for both patient and survey diagnosis. Present availabilities for human diagnosis are reviewed focusing on advantages and weaknesses, sample management, egg differentiation, qualitative and quantitative diagnosis, antibody and antigen detection, post-treatment monitoring and post-control surveillance. Main conclusions refer to the pronounced difficulties of diagnosing fascioliasis in humans given the different infection phases and parasite migration capacities, clinical heterogeneity, immunological complexity, different epidemiological situations and transmission patterns, the lack of a diagnostic technique covering all needs and situations, and the advisability for a combined use of different techniques, at least including a stool technique and a blood technique.